Otolith annulus validation and population dynamics of dark sleeper Odontobutis potamophila: insights for sustainable fisheries management - Miao Xiang; Miao Xiang; Haoran Liu; Haoran Liu; Haoran Liu; Bo Li; Hongxi Guo; Chuankun Zhu; Man Wang; Man Wang; Jie Wang; Jie Wang; et al. (Frontiers in Marine Science, 2025)
In this study, we assessed the growth patterns and population characteristics of the Odontobutis potamophila in Nansi Lake to inform evidence-based management recommendations for the sustainable development of fisheries in the region. A collection of O. potamophila was taken from Nansi Lake between August 2017 and July 2018 (except February) to estimate the age structure, growth pattern, and mortality of the population. Edge-type analysis of sagittal otoliths indicated that a single annulus was formed from March to May. The results revealed that the age structure of O. potamophila consisted of four age groups (0-3 ages), with 0-1 year-old fish comprising about 85.11% of the harvest. An isometric growth pattern was observed, with the Logistic growth function providing the best fit for combined sexes. SLt=172.94/(1+e−0.458(t−0.79))(n=591, R2 = 0.622). Total mortality (Z), natural mortality (M), and fishing mortality (F) were computed as 1.69, 0.53, and 1.16/year, respectively. Meanwhile, the exploitation rate (E) was 0.69/year, in accordance with the rule of thumb (E>0.5, the fish stock was undergoing overfishing), which indicated the stock has been overfished slightly. These results showed that brief generation-time, dominance of juvenile fish and relatively high natural mortality of the O. potamophila provide essential information on the native fish species in Nansi Lake, which may be essential for conservation strategies and artificial propagation. At the same time, these results provide critical data for sustainable fisheries management in Nansi Lake and similar ecosystems.